Disparities in Psychological Traits and Income: Race, Ethnicity, and Gender in the U.S. - Aurelie Dariel; John C. Ham; Nikos Nikiforakis; Jan Stoop (Institute of Labor Economics (IZA), 2024)
There are pronounced racial, ethnic, and gender gaps in income in the U.S. We investigate whether these correspond with differences in competitiveness, risk tolerance, and confidence relative to performance in a large, stratified sample of the U.S. prime-age population. We find substantial differences in all three traits across Black, Hispanic, and White males and females. These traits predict individual income. Competitiveness and risk tolerance help explain the White gender income gap. Competitiveness also affects the Black-White income gap between men. Confidence about one's performance helps explain a substantial and significant portion of all five race-gender income gaps with White men.
Keywords: C90; D03; 330; racial/gender income gaps; overconfidence; competitiveness; risk tolerance